(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background: Polycystic ovary syndrome (PCOS) is a common endocrinopathy characterized by oligo-ovulation or anovulation, signs of androgen excess, and multiple small ovarian cysts. PCOS is thought to be one of the leading causes of female subfertility. Objective:To evaluate and compare the effects of finasteride vs metformin in treatment of PCOS related infertility. Methods:Seventy seven infertile married women with an age range between 18 and 35 years were studied complaining from infertility due to PCOS. They were divided into group 1 treated with finasteride (5 mg daily concomitantly with an oral contraceptive pill "OCP" continuously for 2 months) and group 2 was treated continuously for 3 months with metformin (500 mg three times daily). Results:The percentage of patients responded to metformin treatment was 35.89%, whereas 26.32% of patients were responded to the treatment with finasteride-OCP combination. There were no significant difference between metformin and finasteride in regard to the mean number of mature follicles (1.21±0.43 vs 1.2±0.42) and endometrial thickness (7.26±1.1 vs 7.80±2.25 mm) respectively. The pregnancy rate per patient was higher in metformin treated group in comparison to finasteride treated group (60% vs 21.42%); however, this difference was insignificant (P > 0.05). Conclusion: Finasteride has a good promising effect in the treatment of infertility due to PCOS, as more patients responded to an oral finasteride-OCP combination in comparison to those responded to an oral metformin monotherapy and the difference in the pregnancy rate of the two groups was not significant. Keywords: Finasteride, Metformin, Polycystic ovary syndrome, Infertility